Adult-onset Henoch-Schonlein purpura: A case report - Ruslan, Lettisia Amanda; Saraswati, Putu Dyah Ayu (Bali Dermatology Venereology and Aesthetic Journal, 2024)
Background: Henoch-Schönlein purpura (HSP) is a cutaneous small vessel vasculitis that typically affects children under ten but may also occur in adults. This study aims to report a rare instance of an adult patient with HSP to expand our knowledge and prevent delayed diagnosis and treatment. Case: A 21-year-old female patient presented with palpable purpuric lesions on the lower abdomen, buttocks, and lower limbs. In addition, the patient complained of abdominal pain and joint pain. The patient had suffered an upper respiratory tract infection with spontaneous resolution three days before the skin lesions. Laboratory tests showed leukocytosis and elevated anti-Streptolysin O titer. The patient was diagnosed with HSP and given oral methylprednisolone, antibiotics, and symptomatic treatment. She showed clinical improvement after taking medication. Conclusion: Henoch-Schönlein purpura is typically a self-limiting disease and infrequent in adults, but it has the potential to manifest into life-threatening conditions such as end-stage renal failure. An integrated multidisciplinary approach is needed for early diagnosis and management.